Antiviral Mechanisms of N-Phenyl Benzamides on Coxsackie Virus A9 - Mira Laajala; Kerttu Kalander; Sara Consalvi; Olivier Sheik Amamuddy; Özlem Tastan Bishop; Mariangela Biava; Giovanna Poce; Varpu Marjomäki (MDPI AG, 2023)
Enteroviruses are one of the most abundant groups of viruses infecting humans, and yet there are no approved antivirals against them. To find effective antiviral compounds against enterovirus B group viruses, an in-house chemical library was screened. The most effective compounds against Coxsackieviruses B3 (CVB3) and A9 (CVA9) were CL212 and CL213, two N-phenyl benzamides. Both compounds were more effective against CVA9 and CL213 gave a better EC50 value of 1 µM with high a specificity index of 140. Both drugs were most effective when incubated directly with viruses suggesting that they mainly bound to the virions. A real-time uncoating assay showed that the compounds stabilized the virions and radioactive sucrose gradient as well as TEM confirmed that the viruses stayed intact. A docking assay, taking into account larger areas around the 2-and 3-fold axes of CVA9 and CVB3, suggested that the hydrophobic pocket gives the strongest binding to CVA9 but revealed another binding site around the 3-fold axis which could contribute to the binding of the compounds. Together, our data support a direct antiviral mechanism against the virus capsid and suggest that the compounds bind to the hydrophobic pocket and 3-fold axis area resulting in the stabilization of the virion.